The Rib Metaphor in Hadith: A Study of Meaning and Gendered Social Relevance - Habiba, Siti; Raharusun, Agus suyadi; Kurmalasari, Tety; hanifah , Hanifah (Diroyah : Jurnal Studi Ilmu Hadis, 2025)
This article discusses and analyzes hadiths that address the creation of women. It is stated that women were created from a "crooked" rib. The term crooked carries a negative connotation, such as being deceitful or dishonest, implying that women must always be guided and advised by their husbands or fathers. Can it be accepted that women are seemingly born with inherent negative traits simply because they were created from a crooked rib? Yet, the Prophet Muhammad (SAW) stated that every child is born in a state of purity (fitrah). In this study, the author employs a descriptive qualitative method with a focus on literature review. The findings indicate that both men and women are born in a state of fitrah or purity, and that the rib is a crucial, functional, and perfect part of the human body, created by the Most Perfect. When something is likened to something perfect, it, too, should be seen as perfect as a creation. Not everything that is crooked is necessarily bad or has a negative connotation; the rib itself is originally created with a natural curve or bend. This very shape allows the rib to support and enhance life.